1989
DOI: 10.1192/s0007125000018183
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Early-Onset and Late-Onset Depressive Illness in the Elderly

Abstract: Elderly patients with early-onset and late-onset depressive illness presenting to psychiatrists for treatment were compared for social, demographic, and clinical measures. For most factors measured no statistically significant differences were found. In the early-onset cases, patients were significantly more severely depressed. There was some evidence for the hypotheses that family history is less important and biological factors more important in late-onset depression. It is suggested that the latter hypothes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
1

Year Published

1992
1992
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 21 publications
1
26
1
Order By: Relevance
“…This idea is supported by studies showing a high rate of depression in patients with hypertension, diabetes, coronary disease [30,31] as well as by the frequent occurrence of silent stroke and white-matter changes detected by neuroimaging in LOD [32][33][34]. Other epidemiological [3], clinical [2,6,35] and neuroimaging studies [19,36] support the possibility of a relationship, in certain cases, between late-life depression and AD.…”
Section: Discussionsupporting
confidence: 61%
See 2 more Smart Citations
“…This idea is supported by studies showing a high rate of depression in patients with hypertension, diabetes, coronary disease [30,31] as well as by the frequent occurrence of silent stroke and white-matter changes detected by neuroimaging in LOD [32][33][34]. Other epidemiological [3], clinical [2,6,35] and neuroimaging studies [19,36] support the possibility of a relationship, in certain cases, between late-life depression and AD.…”
Section: Discussionsupporting
confidence: 61%
“…Admission to a hospital or contact with a health care professional for evaluation and treatment of sustained depressive symptoms constituted a depressive episode. The EOD and LOD groups, respectively, included patients who had experienced at least one previous episode of depression before the age of 60 and those who had not [6,18,19].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a subset of elderly depressed patients with major depression, the first episode occurs late in life (Alexopoulos et al, 1988). This subgroup, frequently referred to as having late-onset depression, exhibits certain unique clinical, biological, and neuroimaging characteristics (Burvill et al, 1989;Heun et al, 2000;Krishnan et al, 1995Krishnan et al, , 1997Schweitzer et al, 2002), implying that late-onset depression may represent a distinct subtype of depression in the elderly. Along with observations of greater cognitive deficits (Salloway et al, 1996) and an increased risk of dementia conversion (Geda et al, 2006;Schweitzer et al, 2002), there is some evidence that patients with late-onset depression may have more pronounced atrophy in cortical and subcortical regions implicated in the pathophysiology of elderly depression (Almeida et al, 2002;Hickie et al, 2005;Steffens et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Three such studies [20,21,22] reported a greater increase (relative to controls) of neuroticism in EOD than in LOD, and three [23,24,25] found equal increases of neuroticism in EOD and LOD. Two of the studies employed a methodologically strong community-based longitudinal prospective design with personality measures predicting depressive episodes 3-5 years [20] and 10 years [22] later.…”
Section: Introductionmentioning
confidence: 99%